Maximize the benefits of water sensitive urban designs in a local government area: Western Australia - Kannangara, Dumal; Sarukkalige, Priyantha Ranjan; Botte, M. (International Association of Computer Science and Information Technology (IACSIT), 2012)
Until recently, stormwater management strategies have failed to adequately consider the criticality of spatially varying soil permeability values and their implications on drainage designs. This case study was carried out in new development areas, focusing on identification of soil properties and development of a typology of suitable stormwater management strategies with respect to applicable infiltration capacities. The Guelph Permeameter was used to investigate the in-situ saturated hydraulic conductivities. Test results were categorized into four main permeability groups, very rapid (> 1.56 m/day), rapid (0.48<1.56 m/day), moderate (0.12<0.48 m/day) and slow (<0.12 m/day), based on the theoretical requirements of stormwater management techniques. Finally, with the help of the existing soil maps, the point represent hydraulic conductivity data were been generalized logically in order to develop the hydraulic conductivity maps representing the areal average as an electronic shape files by using a GIS Arc view mapping software. The future development areas under Central Maddington, Kenwick, Central and Outer Beckenham have been identified as low permeable areas which is not suitable for infiltration based stormwater management strategies whereas the Landford, Thornlie, North Huntingdale and Gosnells has been identified as high permeable areas which is highly recommended for infiltration based stormwater management strategies.